PELATIHAN PEMBELAJARAN AKTIF ABAD -21 YANG TERINTEGRASI PADA PROFIL PELAJAR PANCASILA BAGI GURU GURU SD IT PERMATA BERBASIS TEKNOLOGI DAN SAINTIFIK - Palma Juanta; Muhardi Saputra; Anita Anita; Siti Aisyah; Sumita Wardani (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
Abstract: Learning is a process of interaction between students and educators in a learning environment that takes place in an educational manner, so that students can develop their attitudes, knowledge and skills to achieve the goals that have been set. The development of technology every year makes it difficult for teachers to keep up with developments so that almost every teacher still does not understand how to use Microsoft PowerPoint and Excel. Teachers only use the application as a tool. Therefore, there is a need for training for teachers to make learning plans, recap student learning outcomes, or create interesting teaching materials for students that are technologically and scientifically based so that they can improve professional competence, especially in the appropriate use of technology in the learning process.Keywords: teachers; technology; scienceAbstrak: Pembelajaran adalah proses interaksi antara peserta didik dan pendidik pada suatu lingkungan belajar yang berlangsung secara edukatif, agar peserta didik dapat membangun sikap, pengetahuan dan keterampilannya untuk mencapai tujuan yang telah ditetapkan. Berkembangnya teknologi setiap tahunnya membuat para guru kesulitan dalam mengikuti perkembangannya sehingga hampir setiap guru masih kurang paham menggunakan microsoft powerpoint dan excel. Guru hanya menggunakan aplikasi tersebut sebatas pada tools. Maka itu perlu adanya pelatihan bagi guru untuk membuat rencana pembelajaran, merekap hasil belajar peserta didik, atau membuat bahan ajar yang menarik bagi peserta didik yang berbasis teknologi dan saintifik sehingga dapat meningkatkan kompetensi profesional terutama dalam pemanfaatan teknologi pada proses pembelajaran secara tepat.Kata kunci: guru-guru; teknologi; saintifik